Peningkatan Kualitas Produk Makanan pada UKM di Kota Magelang - Rany Puspita Dewi; Trisma Jaya Saputra; Herru Santosa Budiono (Universitas Muhammadiyah Surakarta, 2023)
Small Medium Enterprise (SME) Keripik Talas “Sumber Rejeki” is placed approximately 3.6 km from Magelang and produces taro chips. It has been started production in 2010. One of the production processes that is still done traditionally, is oil draining, so the taro chips produced still have high oil content. The purpose of the activity is to escalate the productivity of SME